Alternative diets among adolescents: facts or fads?. Issue 2 (16th April 2021) - Athanasian, Christian E.; Lazarevic, Bojan; Kriegel, Elana R.; Milanaik, Ruth L.
Abstract : Purpose of review: With rising rates of chronic noninfectious diseases across the United States thought to be associated with the average American diet, many have adopted alternative diets. Most of these diets promise weight reduction via adherence to strict dietary guidelines, often removing certain types of food. With access to a plethora of information online, it is easy for adolescents to become confused when making dietary decisions. Although these diets promise benefits, it is important to understand common shortcomings and how to overcome them for safe implementation among adolescents. Recent findings: This review discusses the theory, implementation, and risks associated with intermittent fasting as well as vegetarian, vegan, ketogenic, Atkins, Paleolithic, and Mediterranean diets. These considerations are further modified for pediatric populations with a focus on the social influences on dieting. Summary: Although these diets may be promising, successful adherence to them requires addressing possible shortcomings associated with a certain diet. Pediatricians should be aware of how these dietary strategies may be properly implemented in order to prevent any harm to the patient. Empowering the patient and their families through informational resources is recommended. Pediatricians should also discuss motivations underlying their patient's dietary changes in order to determine whether these motivations are healthy.